2020
DOI: 10.2139/ssrn.3644348
|View full text |Cite
|
Sign up to set email alerts
|

Switching Costs, Brand Premia and Behavioral Pricing in the Pharmaceutical Market

Abstract: This article examines the market power of branded prescription drugs faced with generic competition. Using prescription-level and matched socioeconomic panel data of the entire Swedish population between 2010 and 2016, I provide evidence for the key role of switching costs. A discontinuity surrounding patent expirations establishes that the effect is causal. Further, by comparing patients with and without medical education, I show that those without medical education experience higher brand premia. A unique fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“… Similarly, Bronnenberg et al (2015) andJanssen (2018) provide evidence on how expert knowledge affects individuals' willingness to pay for branded versus genetic pharmaceuticals.9 McCrary and Royer (2011) also establish a positive effect of maternal education on infant health. Further, Lundborg and Majlesi (2018) exploit a Swedish compulsory schooling reform to document spillovers in the opposite direction, from children's education to parental longevity.…”
mentioning
confidence: 99%
“… Similarly, Bronnenberg et al (2015) andJanssen (2018) provide evidence on how expert knowledge affects individuals' willingness to pay for branded versus genetic pharmaceuticals.9 McCrary and Royer (2011) also establish a positive effect of maternal education on infant health. Further, Lundborg and Majlesi (2018) exploit a Swedish compulsory schooling reform to document spillovers in the opposite direction, from children's education to parental longevity.…”
mentioning
confidence: 99%
“…A third contribution is that the article separates state dependence for individual pharmaceutical brands from heterogeneity that cannot be captured by observables. This complements the work by Feng [2018] and Janssen [2019] by, instead of producing reduced form evidence on state dependence in the dichotomous choice between the brand‐name product and any generic version, estimating state dependence effects on the product level. Compared to Janssen's structural estimation, the contribution of this article includes that it analyzes state dependence on the product level for a large set of drugs (762 exchange groups) and uses instruments to separate state dependence from inertia caused by uncontrolled heterogeneity.…”
Section: Introductionmentioning
confidence: 65%
“…In using this quasi‐experimental approach to identify state dependence, this article relates to Ericson [2014], who used an experiment in which plans for the Medicare Part D Low‐Income Subsidy Program were randomly assigned. It also relates to Coscelli [2000], Iizuka [2012], Chan, Narasimhan and Xie, [2013], and more closely to Feng [2018] and Janssen [2019], who all found inertia in choices among pharmaceuticals. Coscelli [2000] used patients’ switching of physicians to conclude that inertia at the patient level contributed to patients’ being prescribed the same drug repeatedly, even though therapeutic alternatives exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health economic studies in multiple countries have concluded that patients prefer originals and experience history dependence when choosing pharmaceuticals, meaning that they tend to consume products with which they have had a positive experience (Bronnenberg et al, 2015;Feng, 2020;Granlund, 2021;Janssen, 2020). 3 We add to the literature but also highlight that it is possible to break such history dependence.…”
Section: Introductionmentioning
confidence: 87%